The Extinction and Return of Fear of Public Speaking. (November 2016) - Laborda, Mario A.; Schofield, Casey A.; Johnson, Emily M.; Schubert, Jessica R.; George-Denn, Daniel; Coles, Meredith E.; Miller, Ralph R.
Prior studies indicate extinguished fear often partially returns when participants are later tested outside the extinction context. Cues carried from the extinction context to the test context sometimes reduce return of fear, but it is unclear whether such extinction cues (ECs) reduce return of fear of public speaking. Here we assessed return of fear of public speaking, and whether either of two types of ECs can attenuate it. Participants gave speeches of increasing difficulty during an exposure practice session and were tested 2 days later in a different context. Testing occurred in the presence of physical ECs, after mentally rehearsing the exposure session, or without either reminder. Practice reduced fear of public speaking, but fear partially returned at test. Neither physical nor mental ECs reduced partial return of fear of public speaking. The return of extinguished fear of public speaking, although small, was reliable, but not appreciably sensitive to presence of ECs.